The Poetic Interpretation of Babur’s Image in the Views of European and Uzbek Literary Scholars - Anarkulova, Zubayda; Niyadullayeva, Sabrina (The Lingua Spectrum, 2025)
This article provides a comparative analysis of the poetic and artistic interpretation of Zahiriddin Muhammad Babur’s personality from the perspectives of European and Uzbek literary studies. The research examines Babur’s multifaceted nature as a poet, statesman, and human being, focusing on the expression of patriotism, love, humanity, exile, and admiration for the beauty of nature in his lyrical works. Uzbek literary scholars (A. Qayumov, N. Mallayev, I. Haqqulov, and others) interpret Babur’s creativity as a poetic phenomenon imbued with national spirit, sincerity, and folk thought, while European scholars (W. Erskine, A. Beveridge, E.D. Ross, S. Lane-Poole, F. Werfel, R. Godden) regard his works as a spiritual bridge between Eastern and Western cultures, reflecting universality and human values. The article reveals the artistic features of Babur’s lyricism based on the principles of realism, humanism, and naturalness, and analyzes his poetic world in the context of Uzbek and world literature. As a result, Babur’s image is interpreted as a literary phenomenon that glorifies universal values and strengthens intercultural dialogue. Uzbek scholars view Babur as a symbol of national identity and spiritual purity, emphasizing the harmony of sincerity, pure emotions, and philosophical reflection in his poetry. European scholars, on the other hand, consider Babur to be one of the brightest examples of Eastern thought and a universal expression of the human intellect. They regard his Baburnama not only as a historical source but also as a high manifestation of poetic consciousness.